Evolution of Consumption and Retail Transformation – The Emergence of New Institutional Order for the Future of Retailing - Karhu Anna; Pelto Elina; Palmunen Lauri-Matti (Emerald, 2025)
Retailing has developed from independent merchants to multinational giants operating through global value chains, which has profoundly shaped consumption patterns in Western economies. This constant development currently consists of three global-scale change trajectories – climate change, online consumption, and technological development – that affect the retail industry. Based on this, this chapter concentrates on connecting the development paths of consumption and retailing and identifies various factors that affect the future of international retailing. The authors analyze the changes in institutional logics of international retailing by mapping the past, present, and future of the retail industry and consumption using content analysis of secondary data. The authors pay special attention to the effect of the current Covid-19 crisis on the future development of the retail industry. In the findings of this chapter, the authors recognize institutional logics changes in organizing the position of retailing as a connector of customers and producers, and the authors suggest blockchain to be an emerging new institutional order.
International Business in Times of Crisis: Tribute Volume to Geoffrey Jones.